2018
DOI: 10.7759/cureus.2165
|View full text |Cite
|
Sign up to set email alerts
|

What Do Patients Think About Their Radiation Oncologists? An Assessment of Online Patient Reviews on Healthgrades

Abstract: IntroductionAn increasing number of patients search for their physicians online. Many hospital systems utilize Press-Ganey studies as internal tools to analyze patient satisfaction, but independent third-party websites have a large presence online. Patients’ trust in these third-party sites may occur despite a low number of reviews and a lack of validity of patients’ entries. Healthgrades.com has been shown as the most popular site to appear on Google searches for radiation oncologists (ROs) in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
2
10
3
Order By: Relevance
“…In our study, the OR of ROs showed the greatest correlation withbedside manner, accuracy of diagnosis, and spends appropriate time with patients, achieving strong levels of correlation with all three factors (Table 2 ). Our work aligns with previous findings that suggest that physician-related factors show the most direct relationship with the OR of ROs and oncologists [ 6 , 15 - 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, the OR of ROs showed the greatest correlation withbedside manner, accuracy of diagnosis, and spends appropriate time with patients, achieving strong levels of correlation with all three factors (Table 2 ). Our work aligns with previous findings that suggest that physician-related factors show the most direct relationship with the OR of ROs and oncologists [ 6 , 15 - 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we manually searched for self-reported patient data from a popular PRW and observed the majority of patient satisfaction scores for ROs to be in the range of great to excellent. These findings are consistent with our previous work regarding high patient satisfaction with ROs on Healthgrades [ 6 ], patient satisfaction literature examining hand surgeon ratings on three PRWs across the country [ 14 ], and literature on primary care physicians, medical specialists, surgical specialists, and obstetricians and gynecologists who practice in Virginia [ 1 ]. Given the current popularity of PRWs, the findings of this study are directly relevant to patients and ROs and can be viewed as additional data in the growing literature surrounding patient satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A separate study performed by the Journal of the American Medical Association reported that 25% of US adults consulted online physician rating sites, and more than 33% of online viewers went to a physician or avoided one based on their ratings [9]. Furthermore, a recent study analyzed online Healthgrades reviews of 2679 radiation oncologists and found that their “likelihood to recommend to family and friends” score was significantly lower for physicians with fewer numbers of online reviews (<10) compared with colleagues with more than 10 reviews [10]. These are just a few examples that underscore the use of online health information and how public information might influence prospective patients.…”
Section: Discussionmentioning
confidence: 99%